Impact of position of bolster on outcome of prone PCNL—A randomized clinical trial - Vikram Singh; Ishwar Ram Dhayal; Sanjeet Kumar Singh; Alok Srivastava; Nandan Rai (BJUI Compass)
Abstract Objective To determine whether the position of the bolster affects the access tract (supracostal/infracostal) for a superior calyceal puncture during prone PCNL and its effect on pleural complications. Materials and Methods It was a randomized clinical trial. Patients in whom superior calyceal puncture was done were divided into two groups by systematic sampling method, group 1 (horizontal bolster) and group 2 (vertical bolster), 50 patients in each group. Standard PCNL was perfomed in all patients. Chest x‐ray was done on POD 0 (postoperative day) and POD 1 for assessment of pleural complication. NCCT KUB was done on POD 1 for assessment of stone clearance. Results In group 1, 36 patients (72%) underwent supracostal puncture and 14 patients (28%) underwent infracostal puncture while in group 2, 38 patients (76%) underwent supracostal puncture and 14 patients (28%) underwent infracostal puncture (p‐value‐ 0.820). Two patients (4%) in group 1 & three patients in group 2 had pleural complications in the form of hydrothorax (p‐value‐ 0.666). Four patients in group 1 and five patients in group 2 underwent ancillary procedure for clearance of residual stones. Conclusion In our study, the orientation of the bolster either horizontal or vertical does not affect the site of puncture during prone PCNL which probably resulted in no difference in pleural complications in two groups.